EPIC AND RELIGION (Scientific journal of the Fergana State University, 2023)
This article highlights the interpretation of the cult of horses and camels, the naming of children, the unusual birth of the hero are totemistic, shamanic and magical images in the epics "Alpamysh" and "Gurugli", as a result of the spread of Islam among the Turkic peoples living in Central Asia, the interpretation of Islamic views in the epics. The article also scientifically substantiates the fact that epics are an ethnographic source through the ethnological study of information related to family rituals described in the epics of folklore of Southern Uzbekistan.